Can "Caricia" and "Princesa" apples be considered low-chilling cultivars? - Castro, Damian Cesar (2017)
The purpose of this work was to study the response of two apple cultivars bred for low chilling environments to artificial chilling accumulation. Two trials were carried out; in experiment one, excised shoots were randomly taken from "Caricia" and "Princesa", and in experiment two, intact and excised shoots of "caricia", "Princesa" and "Gala" (control) were collected. After collection, both shoot types were exposed to artificial chilling accumulation (4.0 ± 0.5 °C) from 0 to 1200 chill units (CU). Bud break of mixed buds of "Caricia" and "Princesa" was higher than 50% between 0 CU to 1200 CU, irrespective of shoot type. Bud break of "Gala" mixed buds exceeded 50% only in intact shoots after accumulating 900 CU. The mean time to bud break of "Caricia" and "Princesa" diminished with increasing chilling accumulation and stabilized after ~600 CU, depending on the type of shoot and the year of experimentation. The low-chill apple cultivars tested in this work showed shallow dormancy, but they required moderate cold accumulation (800-1150 CU) to fully satisfy their chilling requirements. Thus, although their shallow dormancy makes them suitable for cultivation in chill-deficient environments, they cannot be considered low-chill cultivars.